2008
DOI: 10.1167/iovs.07-0456
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Modulates SDF-1α/CXCR4–Induced Migration of Human Retinal Endothelial Cells (HRECs)

Abstract: This study indicates that curcumin has an inhibitory effect on SDF-1alpha-induced HREC migration. The plausible mechanism of action could be upstream blockage of Ca(2+) influx and the downstream reduction of PI3-K/AKT signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…It was found that angiogenesis and the migration of human retinal endothelial cells induced by SDF-1a were inhibited by curcumin. 42 Caveolin-1 has been shown to play an important role in regulating the activity of eNOS through a direct interaction. 18 Therefore, inhibiting the protein expression of caveolin-1 may contribute to the activation of eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that angiogenesis and the migration of human retinal endothelial cells induced by SDF-1a were inhibited by curcumin. 42 Caveolin-1 has been shown to play an important role in regulating the activity of eNOS through a direct interaction. 18 Therefore, inhibiting the protein expression of caveolin-1 may contribute to the activation of eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] SDF-1 also promotes endothelial tube formation. [31][32][33] We examined the effects of SDF-1 on capillary formation and outgrowth in vitro.…”
Section: Sdf-1 Promotes Capillary Formation In Vitromentioning
confidence: 99%
“…In earlier findings of Fujiwara et al (2008), they demonstrated that curcumin increased the phosphorylation of AMPK and its downstream (Premanand et al 2006). In another study conducted by Sameermahmood et al (2008), they demonstrated that curcumin has an inhibitory effect on stromal cell-derived factor-1 (SDF-1) α-induced HREC migration by reducing downstream PI3K/Akt signals and blocking the upstream Ca 2+ influx (Sameermahmood et al 2008). In the retina of STZinduced diabetic rats, curcumin modulated the oxidatively modified DNA (8-OHdG), glutathione, SODC, and inflammatory parameters, including IL-1β, TNF-α, VEGF, and NF-кB, and may also inhibit the activation of nucleotide excision repair enzymes ).…”
Section: Antidiabetic Role Of Curcuminmentioning
confidence: 87%